Studies of beauty baryon decays toD0ph−and[lambda]+ch−final states - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Hansmann-Menzemer, Stephanie; Jäger, Andreas; Kreplin, Katharina; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2014)
Decays of beauty baryons to the D0ph− and Λ+ch− final states (where h indicates a pion or a kaon) are studied using a data sample of pp collisions, corresponding to an integrated luminosity of 1.0 fb−1, collected by the LHCb detector. The Cabibbo-suppressed decays Λ0b→D0pK− and Λ0b→Λ+cK− are observed, and their branching fractions are measured with respect to the decays Λ0b→D0pπ− and Λ0b→Λ+cπ−. In addition, the first observation is reported of the decay of the neutral beauty-strange baryon Ξ0b to the D0pK− final state, and a measurement of the Ξ0b mass is performed. Evidence of the Ξ0b→Λ+cK− decay is also reported.